1991
DOI: 10.1113/jphysiol.1991.sp018380
|View full text |Cite
|
Sign up to set email alerts
|

Pairing of pre‐ and postsynaptic activities in cerebellar Purkinje cells induces long‐term changes in synaptic efficacy in vitro.

Abstract: SUMMARY1. An in vitro slice preparation of rat cerebellar cortex was used to analyse longlasting modifications of synaptic transmission at parallel fibre (PF)-Purkinje cell (PC) synapses. These use-dependent changes were induced by pairing PF-mediated EPSPs evoked at low frequency (1 Hz) with different levels of membrane polarization (or bioelectrical activities) of PCs for 15 min.2. Experiments were performed on forty-eight PCs recorded intracellularly in a conventional perfused chamber, and in fifty other ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(98 citation statements)
references
References 46 publications
(77 reference statements)
4
93
0
1
Order By: Relevance
“…Armstrong, Edgley, and Lidierth (1988) and Gellman, Gibson, and Houk ( 1985) have shown that the most potent stimulus for climbing fibers is an unexpected sensory event and that similar "reafferent" sensory stimuli resulting from the ani-mal's own actions do not excite the climbing fibers. There is now strong evidence that coincidence of climbing fiber and parallel fiber inputs to Purkinje cells results in longterm depression of the parallel fiber:Purkinje cell synapse (Crepel & Jaillard, 1991 ;Ito, 1989). This may allow the cerebellar cortex to learn or modify a neural representation of the limb dynamics.…”
Section: The Role Of the Inferior Olive In Learningmentioning
confidence: 99%
“…Armstrong, Edgley, and Lidierth (1988) and Gellman, Gibson, and Houk ( 1985) have shown that the most potent stimulus for climbing fibers is an unexpected sensory event and that similar "reafferent" sensory stimuli resulting from the ani-mal's own actions do not excite the climbing fibers. There is now strong evidence that coincidence of climbing fiber and parallel fiber inputs to Purkinje cells results in longterm depression of the parallel fiber:Purkinje cell synapse (Crepel & Jaillard, 1991 ;Ito, 1989). This may allow the cerebellar cortex to learn or modify a neural representation of the limb dynamics.…”
Section: The Role Of the Inferior Olive In Learningmentioning
confidence: 99%
“…Second, a CF-induced rise in Ca 2+ concentration is necessary for LTD because induction of LTD is prevented by injection of Ca 2+ chelators into Purkinje cells (Sakurai 1990;Konnerth et al 1992). Finally, an increase in postsynaptic Ca 2+ concentration is sufficient to produce LTD because direct elevation of Ca 2+ concentration--either by depolarization-induced activation of voltage-gated Ca 2+ channels (Crepel and Jaillard 1991;Linden et al 1991;Kon-nerth et al 1992) or by photolysis of "caged Ca 2+'' compounds (Kasono and Hirano 1994;Lev-Ram et al 1995)--can substitute for activation of the CF synapse. Thus, it is clear that CF activity initiates LTD by elevating postsynaptic Ca 2+ concentration.…”
Section: Introductionmentioning
confidence: 99%
“…However, the PF-PC synapse also needs long-term potentiation (LTP), driven by presynaptic activity without postsynaptic depolarization, to prevent saturation of LTD, allow extinction of learned associations, and refine the temporal precision of learned responses (10)(11)(12). Although a few examples of LTP at the PF-PC synapse had been anecdotally reported in articles focusing on LTD (8,(13)(14)(15)(16), the first systematic characterization of LTP was by Salin et al (17), who stimulated the PFs 120 times at 4-8 Hz and observed a subsequent 40-50% long-term enhancement of excitatory postsynaptic potentials. This work and several subsequent studies have shown that such LTP is induced and expressed presynaptically by means of cAMP signaling (18)(19)(20)(21).…”
mentioning
confidence: 99%